Role of tumor suppressor p53 domains in selective binding to supercoiled DNA - Brázdová, Marie (Oxford University Press, 2002)
We showed previously that bacterially expressed full-length human wild-type p53b(1–393) binds selectively to supercoiled (sc)DNA in sc/linear DNA competition experiments, a process we termed supercoil-selective (SCS) binding. Using p53 deletion mutants and pBluescript scDNA (lacking the p53 recognition sequence) at native superhelix density we demonstrate here that the p53 C-terminal domain (amino acids 347–382) and a p53 oligomeric state are important for SCS binding. Monomeric p53(361–393) protein (lacking the p53 tetramerization domain, amino acids 325–356) did not exhibit SCS binding while both dimeric mutant p53(319– 393)L344A and fusion protein GCN4–p53(347–393) were effective in SCS binding. Supershifting of p53(320–393)–scDNA complexes with monoclonal antibodies revealed that the amino acid region 375–378, constituting the epitope of the Bp53-10.1 antibody, plays a role in binding of the p53(320–393) protein to scDNA. Using electron microscopy we observed p53–scDNA nucleoprotein filaments produced by all the C-terminal proteins that displayed SCS binding in the gel electrophoresis experiments; no filaments formed with the monomeric p53(361– 393) protein. We propose a model according to which two DNA duplexes are compacted into p53–scDNA filaments and discuss a role for filament formation in recombination.